Hydralazine-associated adverse events: a report of two cases of hydralazine-induced ANCA vasculitis - Zuckerman, Roman (J Bras Nefrol, 2018)
Hydralazine is a direct-acting vasodilator, which has been used in treatment for hypertension (HTN) since the 1950s. While it is well known to cause drug-induced lupus (DIL), recent reports are indicating the emergence of the drug-induced anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis (DIV). Herein, we describe two patients (aged 57 and 87 years) who presented with severe acute kidney injury (AKI), proteinuria, and hematuria. Both were receiving hydralazine for the treatment of hypertension. ANCA serology was positive in both patients along with anti-histone antibodies (commonly seen in drug-induced vasculitis). Renal biopsy revealed classic crescentic (pauci-immune) glomerulonephritis in these patients and hydralazine was discontinued. During the hospital course, the 57-year-old patient required dialysis therapy and was treated with steroids and rituximab for the ANCA disease. Renal function improved and the patient was discharged (off dialysis) with a serum creatinine of 3.6 mg/dL (baseline = 0.9 mg/dL). At a follow-up of 2 years, the patient remained off dialysis with advanced chronic kidney disease (CKD) (stage IIIb). The 87-year-old patient had severe AKI with serum creatinine at 10.41 mg/dL (baseline = 2.27 mg/dL). The patient required hemodialysis and was treated with steroids, rituximab, and plasmapheresis. Unfortunately, the patient developed catheter-induced bacteremia and subsequently died of sepsis. Hydralazine can cause severe AKI resulting in CKD or death. Given this extremely unfavorable adverse-event profile and the widespread availability of alternative anti-hypertensive agents, the use of hydralazine should be carefully considered.